Oral contrast radiography evaluation in adhesive intestinal obstruction - Abdulla, Faheem Ahmed; Mohandas, P. G.; Sasi, M. P. (International Journal of Research in Medical Sciences, 2017)
Background: Adhesive small bowel obstruction (ASBO) is a common cause for admission in the surgery casualty. Non-operative management is initially recommended unless there is suspicion of complication, but its optimal duration is controversial. The aims of this study were to evaluate the usefulness of radiographic small bowel examination with contrast medium to predict the need for surgery in ASBO and to decrease late-surgery morbidity. Methods: This prospective observational study was carried out in a tertiary apex institute in Kerala, India enrolling 50 patients with clinical and radiological features of adhesive SBO. The past surgical history, as well as clinical picture, blood tests and radiological findings in these patients were studied. Fifty millilitres of 5% barium suspension were given via naso-gastric tube, and plain abdominal radiographs were taken at 6 and 24 hours afterwards. The primary variable assessed was the presence/absence of contrast in right colon. Surgical intervention was decided upon, based on the treating surgeon’s discretion. Results: In 36 patients, barium contrast appeared in the right colon. In the remaining 14 patients, no evidence of barium contrast in the right colon was seen, and 8 of them underwent surgery, while the other 6 were treated conservatively. There was a statistical significant relationship (p<0.01) between the presence of contrast medium in the right colon and being treated conservatively. There was also a statistically significant (p<0.05) relationship between index case being one for malignancy and undergoing laparotomy for ASBO in the study. Conclusions: Early oral administration of a radiological contrast medium in patients with adhesive small bowel obstruction can effectively predict the need for a surgical procedure. It can shorten not only hospital stay, but also the potential morbidity of late surgery, secondary to a prolonged and unsuccessful non-operative treatment.